The effects of Tualang Honey Supplement on Medial Prefrontal Cortex Morphology and Cholinergic System in Stressed Ovariectomised Rats - Al-Rahbi, Badriya; Zakaria, Rahimah; Othman, Zahiruddin; Hassan, A.; Ahmad, A.H. (Healthy Synergies Publications, 2008)
This study evaluated the effects of Tualang honey on the medial prefrontal cortex (mPFC) morphology and the brain cholinergic system in stressed ovariectomised (OVX) rats. Sixty female Sprague-Dawley rats were divided into six groups: (i) unstressed sham-operated control rats, (ii) stressed sham-operated control rats, (iii) nonnstressed OVX rats, (iv) stressed OVX rats, (v) stressed OVX rats treated with 17 β- oestradiol (20 μg daily, sc) and (vi) stressed OVX rats treated with Tualang honey (0.2 g/kg body weight, orally). After social instability stress, the rats were sacrificed, and the right and left brain hemispheres were isolated for histological studies and estimation of acetylcoline (ACh) and acetylcholinesterase (AChE) concentrations. Stressed OVX rats showed reduced concentrations of ACh and increased AChE in the brain homogenates compared with nonstressed sham-operated controls and the effects were reversed after treatment with either 17 β-oestradiol or Tualang honey. The arrangement and number of Nissl positive cells in the mPFC neurons were significantly improved in stressed OVX rats treated with either 17 β-oestradiol or Tualang honey compared to untreated stressed OVX rats. In conclusion, treatment with either 17 β- oestradiol or Tualang honey significantly improved the morphology of mPFC, increased ACh and reduced AChE concentrations in stressed ovariectomised rats.